Environmental and Biological Factors Shaping Fish Swimming Ability: Insight From a Meta‐Analysis on Endemic Fish in China - Yuanming Wang; Hongtao Wang; Pengcheng Li; Xintong Li; Ruifeng Liang; Kefeng Li (Reviews in Aquaculture, 2026)
Fish swimming ability serves as a robust proxy for physiological assessment and species conservation. Numerous rivers with a large spatial span and diverse fish species in China complicate the efforts to understand swimming ability and challenge the protection of fish populations. One hundred and sixty‐four relevant studies over the past 15 years, involving 30 families and 126 distinct test sites, were identified to provide a comprehensive overview of fish swimming ability in China. Specifically, test sites geographically concentrated in the Yangtze River basin and Cyprinidae received the most research attention. The basin, family, altitude, living condition, and body length exerted considerable effects on fish swimming ability. Fish from the continental basin had the highest induced swimming speed ( U ind ), whereas those from the southwest basin showed outstanding critical ( U crit ) and burst ( U burst ) swimming speeds. U ind did not differ significantly at the family level, while Cyprinidae and Cobitidae outperformed other families in U crit and U burst . U ind was lowest at an altitude of 2328–3588 m, while U crit and U burst followed unimodal trends, peaking at altitudes of 622–1343 m. Test apparatus and protocols had a limited effect on fish swimming ability, only except that swimming speeds in Brett‐type flumes were higher than that in pipe channels or straight flumes. The living condition did not affect U ind while wild Cyprinidae exceeded cultured Cyprinidae in U crit and U burst . Overall, this study identified factors contributing to fish swimming ability differences and their variation patterns, deepening our knowledge on fish swimming ability and informing fish conservation strategies in China.